KEVALIDAN DAN KEPRAKTISAN MEDIA PEMBELAJARAN LEMBAYUNG PADA KEMAHIRAN MENULIS TEKS SURAT RESMI FASE D - Fiqori Agussintia, Tiara; Legi Elfitra; Harry Andheska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop Lembayung learning media for writing formal letter text skills in Phase D at SMP Negeri 2 Tanjungpinang for the academic year 2025/2026. The type of research and development used is the Hannafin & Peck model which involves the stages of needs assessment, design, and development and implementation. Data collection techniques include interviews, validation questionnaire sheets, and practicality questionnaire sheets. Data analysis techniques were carried out using qualitative descriptive and quantitative descriptive methods. The validation results by media experts obtained a score of 98% with very valid qualifications and the validation results by material experts obtained a score of 98% with very valid qualifications. Then, the practicality trial results for small group students obtained a score of 93.33% with very practical criteria and the practicality trial results for large group students obtained a score of 94.9% with very practical criteria.